The rape law in Malaysia from shariah perspective: the need for harmonisation - Nur Aina, Abdullah; Haneef, Sayed Sikandar Shah (Penerbit USIM, Universiti Sains Islam Malaysia, 2018)
According to sections 375 of Malaysia Penal Code, rape is defined as an unlawful sexual intercourse between a man and a woman without the latter’s consent and against her will. The latest amendments to section 375 and 376 Penal Code were made in 2014. However, from the statistical data obtained by the Royal Malaysian Police (PDRM), the number of rape cases are still staggeringly on the rise. Therefore, the application of such a law raises numerous juridical questions. Accordingly, the main purpose of this paper is to analyse the rape law in Malaysia based on the most crucial issues that have been discussed in the related journals, articles and books. Rape law in Malaysia involves three main issues: First; the rapist being under the age of thirteen, Second; the issue of girls age of consent in statutory rape, Third; the rape punishment. The methodology of this paper is using an exploratory qualitative research approach and adopting the content analysis design. The data is collected from the related journals, articles and books. It is analysed thematically and assisted by computer software tool, Atlas.ti, to make it more efficient. The statistical data obtained from the Royal Malaysian Police (PDRM) are also analysed to support the main data. The findings show that there is a serious need to reform the rape law in order to curb the rape problem and protect the lineage (hifz al-nasl). This paper proposes that the solution lies on harmonization between the Malaysia rape law and the Shariah principles on the three main issues as mentioned above.